2017
DOI: 10.1186/s41476-017-0047-7
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the optical properties of a laser pulse at λ = 1.55μm in InGaAs\InP double coupled quantum well nanostructure

Abstract: Background: The transient and steady-state behaviour of the absorption and the dispersion of a probe field propagating at λ = 1.55μm through an InGaAs\InP double coupled quantum well are studied. The effect of terahertz signal excitation, electron tunnelling and incoherent pumping on the optical properties of the probe field is discussed. Methods: The linear dynamical properties of the double coupled quantum well by means of perturbation theory and density matrix method are discussed. Results: We show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Under this approximation, the iterative perturbative technique has been applied on the density matrix elements in equation (6). To be specific, we have expanded the density matrix elements in BSR as a power series of perturbation strength factor m (0 m 1) [25] ˜˜˜˜( )…”
Section: Analytical Steady-state Solutions Using Perturbative Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Under this approximation, the iterative perturbative technique has been applied on the density matrix elements in equation (6). To be specific, we have expanded the density matrix elements in BSR as a power series of perturbation strength factor m (0 m 1) [25] ˜˜˜˜( )…”
Section: Analytical Steady-state Solutions Using Perturbative Techniquementioning
confidence: 99%
“…Electromagnetically induced transparency (EIT) [1][2][3][4] is one such phenomenon where coherent interaction of lasers with atomic system can reduce the absorption of the medium at resonant probe transition in presence of strong coupling field. EIT phenomenon has several applications in the field of slowing of light in quantum information [5][6][7][8][9][10], lasing without inversion (LWI) [11], enhanced non-linear optics [1], high-resolution spectroscopy [12], etc. Another analogus counter phenomenon of EIT is electromagnetically induced absorption (EIA) [13,14], where the system becomes highly absorptive by adjusting the strengths of applied laser fields.…”
Section: Introductionmentioning
confidence: 99%
“…Subluminal and superluminal light propagation has been discussed in various atomic systems and it has been shown that switching from subluminal to superluminal (or vice versa) can be achieved with the intensity of coupling fields, the relative phase of applied fields and an incoherent pumping field [19][20][21][22]. In addition, a new model for controlling the optical properties of the light pulse via the quantum coherence Laser Physics Slow and fast light propagation and controllable switch at λ = 1.55 µm in a photonic crystal with a defect layer doped by an InAs/GaAs quintuple-coupled quantum dot molecule nanostructure effect in a semiconductor heterostructure was proposed very recently [23][24][25][26][27]. It was noted that the incoherent pumping field and the tunneling effect can be used as potential parameters for adjusting the transient and steady-state behavior of light beams [27].…”
Section: Introductionmentioning
confidence: 99%